Preparation and assessment of a self‐healing material based on microcapsules filled with ethyl phenylacetate. Issue 20 (10th February 2016) - Ma, Wanpeng; Zhang, Wei; Zhao, Yang; Yu, Helong
ABSTRACT: A self‐healing material was developed on the basis of a biological system. The self‐healing epoxy resin, which incorporated microcapsules filled with ethyl phenylacetate (EPA), was investigated. The microcapsules were prepared by an in situ polymerization method. The microcapsule‐formation process was monitored by optical microscopy, and the surface morphology was observed by scanning electron microscopy (SEM). The self‐healing performance of the epoxy resin was assessed by manual and in situ healing experiments. We investigated the effects of the healing time, amount of EPA, and degree of curing of matrix on the healing performance by manually injecting EPA into the crack plane. The maximum healing efficiency was obtained within 24 h. The swelling curve was overlaid onto the healed load plot; this indicated that crack healing was achieved as a result of solvent diffusion. The healing load reached the maximum value when the amount of EPA was 0.5 μL and was capable of filling the crack volume. Moreover, the healing performance was related to the degree of swelling. The in situ healing efficiency was dependent on the microcapsule concentration. The fracture toughness could be fully restored when the microcapsule concentration was 10%. Finally, the crack interface was analyzed with SEM. The results show that the fracture line was difficult to detect, and this suggested complete crack healing by EPA. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43430. Abstract :